1998
DOI: 10.1073/pnas.95.12.7169
|View full text |Cite
|
Sign up to set email alerts
|

Nedd4 mediates control of an epithelial Na + channel in salivary duct cells by cytosolic Na +

Abstract: Epithelial Na ؉ channels are expressed widely in absorptive epithelia such as the renal collecting duct and the colon and play a critical role in f luid and electrolyte homeostasis. Recent studies have shown that these channels interact via PY motifs in the C terminals of their ␣, ␤, and ␥ subunits with the WW domains of the ubiquitin-protein ligase Nedd4. Mutation or deletion of these PY motifs (as occurs, for example, in the heritable form of hypertension known as Liddle's syndrome) leads to increased Na ؉ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 40 publications
(81 reference statements)
5
114
1
Order By: Relevance
“…Third, mutation of ENaC PY motifs (which bind to Nedd4-2) did not prevent Na ϩ from inhibiting ENaC cleavage. These findings contrast with previous observations in oocytes and salivary duct cells that implicated a role for Nedd4 and ENaC PY motifs in the inhibition of ENaC by intracellular Na ϩ (13,36). Thus, it seems likely that intracellular Na ϩ regulates ENaC activity by more than one mechanism.…”
Section: Figure 5 Nacontrasting
confidence: 56%
“…Third, mutation of ENaC PY motifs (which bind to Nedd4-2) did not prevent Na ϩ from inhibiting ENaC cleavage. These findings contrast with previous observations in oocytes and salivary duct cells that implicated a role for Nedd4 and ENaC PY motifs in the inhibition of ENaC by intracellular Na ϩ (13,36). Thus, it seems likely that intracellular Na ϩ regulates ENaC activity by more than one mechanism.…”
Section: Figure 5 Nacontrasting
confidence: 56%
“…In both experimental systems, the transport of Na ϩ and the transport of Cl Ϫ thus seem to be linked in some way. Interestingly, changes in [Cl Ϫ ] i have recently been shown to influence epithelial Na ϩ channel activity in some systems (8,22). It is therefore possible that the apparent coupling between Na ϩ and Cl Ϫ transport (16,29) may, at least in part, be due to [Cl Ϫ ] i -dependent control of G Na ϩ.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, however, that rapid changes in G Na ϩ might occur in intact cells, since permeabilizing the basolateral membrane could allow the loss of a cytoplasmic component essential to the regulation of G Na ϩ. Indeed, recent work has shown that ENaC can be rapidly controlled via changes in internal [Na ϩ ] and [Cl Ϫ ] (8,22), and it is very unlikely that such ionic control of G Na ϩ (8,22) would be detected in studies of basolaterally permeabilized cells. In this experimental situation, transient changes in internal ionic composition may occur as apical conductances are activated, but the relatively large volume of the external solution implies that such changes would be rapidly compensated for by ions entering/leaving the cytoplasm via the permeabilized membrane (21).…”
Section: Discussionmentioning
confidence: 99%
“…NEDD4-2 (neural precursor cell expressed, developmentally down-regulated 4-2) and a structurally related protein, NEDD4, have been shown to interact with the epithelial sodium channel, and to down-regulate its activity via the ubiquitin-proteasome pathway [23][24][25][26][27][28][29][30][31]. In the present study, we identified NEDD4-2 as a novel binding partner of Smad7, and examined the function of NEDD4-2 in TGF-β superfamily signalling.…”
Section: Introductionmentioning
confidence: 91%